Inclusive business models : touching lives and creating livelihoods - Mukherji, Sourav (Cambridge : Cambridge University Press, 2021)
Inclusive Business Models talks about organizations that employ principles of business to address the needs of the poor. It takes an analytical approach to derive insights about business models by comparison with other inclusive models seen within the same sector and through comparisons with models from a different sector. This cross sector comparison, especially with a number of case studies, would enable readers to cumulate their learning, and act as a guide to management students, practicing managers and entrepreneurs for understanding and analyzing any business model that intends or claims to be inclusive. This book is beneficial for students of entrepreneurship, social enterprises and human resource management. Sections of this book would be relevant for courses on social enterprises, developmental economics and inclusive business models taught globally, given that India today has emerged as a hotbed of experiments and innovations to deal with the problems of poverty and inequality.
Title from publisher's bibliographic system (viewed on 30 Jul 2021).
Keywords: Social responsibility of business -- India; Sustainable development -- India; Public-private sector cooperation -- India; Poverty -- India; Social entrepreneurship -- India